2003
DOI: 10.1111/j.0105-1873.2003.00192.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative risk assessment for the induction of allergic contact dermatitis: uncertainty factors for mucosal exposures

Abstract: The quantitative risk assessment (QRA) paradigm has been extended to evaluating the risk of induction of allergic contact dermatitis from consumer products. Sensitization QRA compares product-related, topical exposures to a safe benchmark, the sensitization reference dose. The latter is based on an experimentally or clinically determined 'no observable adverse effect level' (NOAEL) and further refined by incorporating 'sensitization uncertainty factors' (SUFs) that address variables not adequately reflected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…[15][16][17] It has also been suggested that manufacturers may not take into consideration this increased susceptibility to irritant and allergic contact dermatitis of mucosal surfaces when performing pre-marketing testing. 16,17 Although most patients reported using topical corticosteroids, there were only two positive reactions to the corticosteroid allergens tixocortol pivalate and hydrocortisone-17-butyrate. These are representatives from groups A and D of the allergic contact dermatitis cross-reactive groups in corticosteroid patch testing.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] It has also been suggested that manufacturers may not take into consideration this increased susceptibility to irritant and allergic contact dermatitis of mucosal surfaces when performing pre-marketing testing. 16,17 Although most patients reported using topical corticosteroids, there were only two positive reactions to the corticosteroid allergens tixocortol pivalate and hydrocortisone-17-butyrate. These are representatives from groups A and D of the allergic contact dermatitis cross-reactive groups in corticosteroid patch testing.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,11,14 This finding could be explained by either the frequent use of corticosteroids to treat anogenital conditions or by enhanced penetration. 18,19,32,33 Feldmann and Maibach 34 showed that carbon 14 hydrocortisone penetrates the scrotum at a rate 42 times higher than in the ventral forearm. Similarly, Britz et al 35 showed that 7.7% of topically applied hydrocortisone cream penetrated vulvar epithelium compared with 1.3% used on forearm skin.…”
Section: Commentmentioning
confidence: 99%
“…They take into account interindividual susceptibility, matrix differences between the intended product formulation and the test solution in the existing testing for contact sensitization, and variations in the skin exposures. More conservative uncertainty factors are recommended for the skin exposure considerations if the ingredient is intended for products that will come into contact with mucous membranes [17].…”
Section: Assessing Ingredients For Contact Sensitization Potentialmentioning
confidence: 99%